Hiccups induced by aripiprazole combined with sertraline in an adolescent with olfactory reference disorder: A case report - Li, Zhe; Xiong, Zhenzhen; Jiang, Xingmei; Li, Zhixiong; Yuan, Yiwen; Li, Xiao (Frontiers in Psychiatry, 2022)
Background Hiccup can cause significant distress to patients and affect medication compliance. Individuals with olfactory reference disorder (ORD) who might develop persistent hiccups when treated with a combination of antidepressant and antipsychotic, leading to significant distress and impairment. Case Summary We report a rare case of an adolescent with ORD who was treated with aripiprazole combined with sertraline and who began to hiccup persistently after 6 days on this treatment. He stopped hiccupping after the aripiprazole had been suspended for 12 h. After discharge, the patient continued on sertraline alone and reported no hiccupping at one-month follow-up. Conclusion Clinicians should consider that the combination of aripiprazole and sertraline can induce hiccups during the acute administration period in adolescents with ORD.